Surgical resection of intracranial cavernous hemangioma located at uncommon location: Clinical presentation and management - Li, Jiuhong; Zhang, Guisheng; Ma, Qiang; Li, Xiang; He, Jiaojiang (Frontiers in Neurology, 2023)
Background Intracranial cavernous hemangiomas (CHs) usually originate from the cerebral and cerebellar hemispheres, while the clinical features and optimum treatment of CHs that originate from atypical locations remain unclear. Methods We conducted a retrospective analysis of CHs that originated from the sellar, suprasellar, or parasellar region, the ventricular system, the cerebral falx, or the meninges in patients who underwent surgery from 2009 to 2019 in our department. Results In our study, fourteen patients with pathologically confirmed CHs in uncommon locations (UCHs) were enrolled; 5 were located at the sellar or parasellar region, 3 at the suprasellar region, 3 at the ventricular system, 2 at the cerebral falx, and 1 originated from parietal meninges. The most common symptoms were headache and dizziness (10/14); however, none presented with seizures. All UCHs located in the ventricular systems and 2 of the 3 UCHs located in the suprasellar region manifested as hemorrhagic lesions and shared similar radiological features compared with axial CHs; other locations of UCHs did not have a “popcorn” appearance on T2-weighted image. Nine patients achieved GTR, 2 achieved STR, and 3 achieved PR. Four out of five patients who received incomplete resection underwent adjuvant gamma-knife radiosurgery. During the average follow-up of 71.1 ± 43.3 months, no patient died and one patient encountered recurrence and de novo formation of midbrain CH. Most patients had an excellent KPS score of 90–100 (9 of 14) or a good KPS score of 80 (1 of 14). Conclusion We suggest that surgery is the optimum therapeutic method for UCHs located at the ventricular system, dura mater, and cerebral falx. Stereotactic radiosurgery plays an important role in the treatment of UCHs located at the sellar or parasellar region and remnant UCHs. Favorable outcomes and lesion control could be achieved by surgery.